Guidelines and standards for environmental pollution control in Nigeria - Federal Environmental Protection Agency (Nigeria : Federal Environmental Protection Agency (FEPA), 1991)
These guidelines and standards are set to ensure that industrial activities and wastes management practices are compatible with the overall goal of bequeathing a clean and safe environment to present generations of Nigerians and those unborne
nmn, 28/03/19
Arch
Keywords: Environmental pollution; Environmental pollution - guidelines; Nigeria